Impact of Improved Stoves on Indoor Air Quality in Ulaanbaatar, Mongolia - Cowlin, Shannon; Kaufmann, Rachel B.; Edwards, Rufus; Smith, Kirk R. (World Bank, Washington, DC, 2014)
Ulaanbaatar, Mongolia, is the coldest capital city in the world, with average winter low temperatures of -20° Celsius. Many families there live in gers, traditional Mongolian dwellings consisting of a wooden frame beneath several layers of wool felt. In the ger districts of Ulaanbaatar, cooking and heating energy is provided through indoor coal combustion in metal stoves with chimneys, and in wintertime, such stoves may be in use both day and night. Over the last several years, new stove designs with improved fuel efficiencies have been introduced into many homes. To test the impact of the improved stoves on indoor air quality, 24-hour monitoring of particulate matter (PM) and carbon monoxide (CO) was done in 65 Mongolian gers. The primary analyses focused on 58 households, 20 with original (or traditional-type) stoves, 18 with the improved stove type TT-03, and 20 with the improved stove type G2-2000. In addition to indoor pollutant concentrations, information on other relevant factors was collected, which included home sizes, indoor and outdoor temperatures, age of stove in use, amount of fuel used and number of refuelings, position of monitors relative to chimneys, and number of cigarettes smoked in the home. Analysis of variance showed that these factors did not differ significantly by stove type except that traditional stoves tended to be older than improved stoves. Multivariate regression methods were used to test for statistically significantly different indoor PM and CO concentrations between homes with different stove types while controlling for selected characteristics.